Sistema embarcado Linux para monitoramento em nuvem aplicado a bombeamento fotovoltaico - Dupont, Ivonne Montero (2017)
Commercial data acquisition systems (DAS) often have high costs and complex monitoring, and it is difficult to develop new features according to customer needs. In this sense, the main objective of this dissertation is the development of embedded Linux (Embedded Linux System) Cloud Monitoring System using free software. The data acquisition unit is composed of an Analog / Digital Converter Embedded System, an ESL developed on Raspberry Pi (Rpi) that sends the data collected from the sensors to an interface between the acquisition and Cloud services. In the present research, a photovoltaic (PV) pumping plant installed in the Alternative Energies Laboratory (LEA) located at the PICI Campus of the Federal University of Ceará (UFC) in Fortaleza - CE / Brazil is used. This work presents a comparative analysis between the developed DAS and a commercial data acquisition and supervision system (commercial DAS); with the purpose of studying the strengths and weaknesses of the new system compared to one already consolidated in the market. The measurements of the developed SAD were compared with the same information collected by the commercial DAS installed in the LEA; showing in all cases, a similar behavior between the curves of the parameters compared. The small size of the device and its connection to Cloud Monitoring and the use of Internet of Things (IoT) are determining factors for its use in several areas; allowing increasing our ability to collect, analyze and distribute data in real time. The proposed online monitoring architecture can be applied to decentralized electricity microgeneration projects from various renewable energy sources, contributing to the diversification tendency of the world electricity production.